Maternal Oral Bacterial Levels Predict Early Childhood Caries Development. (March 2014) - Chaffee, B.W.; Gansky, S.A.; Weintraub, J.A.; Featherstone, J.D.B.; Ramos-Gomez, F.J.
Objective : To calculate the association of maternal salivary bacterial challenge (mutans streptococci [MS] and lactobacilli [LB]) from pregnancy through 24 months' postpartum with child caries incidence (≥1 cavitated or restored teeth) at 36 months. Materials & Methods : Dental, salivary bacterial, sociodemographic, and behavioral measures were collected at three- to six-month intervals from a birth cohort of low-income Hispanic mother-child dyads ( N = 243). We calculated the relative child caries incidence, adjusted for confounding, following higher maternal challenge of MS (>4500 colony-forming units per milliliter of saliva [CFU/mL]) and LB (>50 CFU/mL) based on multivariable models. Results : Salivary MS and LB levels were greater among mothers of caries-affected children versus caries-free children. Mothers with higher salivary MS challenge were more likely to have MS-positive children (>0 CFU/mL), but maternal LB challenge was not a statistically significant predictor of child LB-positive status. Adjusting for sociodemographics, feeding and care practices, and maternal dental status, higher maternal salivary challenge of both MS and LB over the study period predicted nearly double the child caries incidence versus lower MS and LB (cumulative incidence ratio: 1.9; 95% confidence interval: 1.1, 3.8). Conclusion : Maternal salivary bacterial challenge not only is associated with oral infection among children but also predicts increased early childhood caries occurrence.